Effect of cultural management on yield and yield attributes of rice in laterite soil - Bridgit, T.K.; Potty, N.N. (Journal of Tropical Agriculture, 2006)
Studies conducted to analyse the pathway of yield formation as influenced by varying cultural management systems in laterite soils revealed that depth of digging at 15 cm or 30 cm or increasing the levels of farm yard manure beyond 5 t ha"1 had only marginal effects on improving the growth and productivity of the plant. Crops under dry seeded condition which did not have reduced soil environment in the early stage manifested better growth as evidenced by higher elongation and more tillers with a steady declining tiller count. Larger numbers of longer roots were another characteristic. As against this, the plants in the reduced environment were comparatively dwarf, tiller production was low but extended beyond maximum tillering and panicle initiation stages and root production was also hindered. The variation in these characters between the two environments worked out to be 46.0 per cent in tiller count and 43.9 per cent in root count. This difference was manifested in the yield levels of 6496 kg ha"1 in dry seeded and 4715 and 4615 in wet seeded and transplanted situations.